Optical spectroscopic studies on the complexation of stilbazolium dyes with a water soluble pillar[5]arene1. Issue 34 (15th April 2015) - Bojtár, Márton; Szakács, Zoltán; Hessz, Dóra; Kubinyi, Miklós; Bitter, István
<x xml:space="preserve">Abstract</x> The host–guest interactions of carboxylato-pillar[5]arene (WPA5) and three stilbazolium dyes were studied by optical spectroscopy. A fluorescence indicator displacement based on WPA5 was shown to detect paraquat in aqueous solution.